Prevention of sufentanil-induced cough during induction of general anesthesia by low-dose esketamine - Xueyue Zhou; Chaoping Guo; Boyu Liu; Yongqing Guan; Shengxiang Wang; Jun Ji (BMC Anesthesiology)
Abstract Background Sufentanil is commonly used to induce general anaesthesia due to its rapid onset of action, strong analgesic effect, long-lasting effect, and stable haemodynamics; however, it often induces cough, increasing the risk of anaesthesia. This study aimed to investigate the preventive effect of low-dose esketamine on sufentanil-induced cough. Methods This randomised, double-blind, placebo-controlled clinical study was conducted at the Air Force Medical Center between September 2023 and May 2024. A total of 100 adult patients (ASA of Anaesthesiologists class I–II) required general anaesthesia for elective surgery. The patients were randomly assigned to two groups: the esketamine group (Group E, n = 50), receiving 0.2 mg/kg esketamine intravenously, and the control group (Group C, n = 50), receiving an equal volume of normal saline. The incidence and severity of sufentanil-induced cough were assessed 1 min after administering of 0.5 μg/kg sufentanil intravenously. Heart rate (HR), mean arterial pressure (MAP), and adverse reactions were recorded at four time points: before esketamine administration (T0), 3 min after esketamine administration (T1), 1 min after endotracheal intubation (T2), and 3 min after endotracheal intubation (T3). The results were analyzed using appropriate statistical methods. Results A total of 100 eligible patients were screened, of which 99 participated in this study (1 patient refused to participate), 50 in Group E, and 49 in Group C. The incidence of cough in Group E (6.0%) was significantly lower than that in Group C (34.7%) (P < 0.001), and the severity of cough was also significantly milder than that in Group C (P = 0.038). The differences in the HR and MAP levels at T0, T1, T2, and T3 between the two groups were not statistically significant (P > 0.05). Two patients in Group C experienced chest wall stiffness, while no adverse reactions were observed in Group E. The difference in the incidence of adverse reactions between the two groups was not statistically significant (P > 0.05). Conclusion Low-dose esketamine (0.2 mg/kg) can significantly reduce the incidence of sufentanil-induced cough during the induction of general anaesthesia in patients, with a small impact on haemodynamics, no adverse reactions, and good safety.